2021
DOI: 10.1186/s12912-021-00607-1
|View full text |Cite
|
Sign up to set email alerts
|

Caregivers’ perception of the caring challenges in coronavirus crisis (COVID-19): a qualitative study

Abstract: Background The nurses act as the guardians of people’s health by preventing, controlling, and curing emerging diseases, including coronavirus, a highly infectious and contagious disease which has presented the caregivers in the Iranian healthcare system with many clinical challenges. In view of lack of research on the clinical challenges which arise during health crises, emerging diseases included, there is need for further investigation of those clinical challenges and dilemmas. The aim in pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 23 publications
4
27
0
Order By: Relevance
“…Consistent with the present study, these nurses have reported moderate anxiety and moderate resilience, and there was an indirect relationship between resilience and anxiety [ 25 ]. Similarly, Ozguc et al (2021) reported that nurses in COVID-19 wards suffered from high levels of death anxiety.…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with the present study, these nurses have reported moderate anxiety and moderate resilience, and there was an indirect relationship between resilience and anxiety [ 25 ]. Similarly, Ozguc et al (2021) reported that nurses in COVID-19 wards suffered from high levels of death anxiety.…”
Section: Discussionsupporting
confidence: 89%
“…In a study conducted in Iran, stressful work environment, doubts on the occurrence of unexpected conditions, lack of support received from officials, and lack of adequate equipment were among the challenges experienced by the nurses who provided healthcare to the patients infected with COVID-19. In addition, staff shortage and lack of equipment were indicated to affect the quality of nursing care [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of previous studies performed in Iran showed that nurses in COVID ward mostly experienced high anxiety. Based on the participants' experiences, Corona anxiety leads to fatigue, decreased concentration, sleep disturbance, decreased resilience, and burnout; also, it threatens the nurses' mental safety [ 17 20 ]. Also, Felice et al (2020) in Italy stated that healthcare workers, especially women who work in high-risk wards, reported an increase in workload and the need for more psychological support during the COVID-19 pandemic [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of the 70 included studies, nineteen were from China (13,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39), sixteen were from Iran (9,11,12,(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52), eight were from Turkey (53)(54)(55)(56)(57)(58)(59)(60), seven were from US (61-67), three were from Italy (10,14,68), two were from Spain (69, 70), two were from South Korea (16,71), two were from Canada (72, 73), two were from Brazil (74,75), two were from the Philippines (76,77), and the remaining seven were from Japan, Thailand, Indonesia, Demark, Leba...…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…In order not to worry their family, some of them hid the fact that they worked in the front line from their family (34,50,53). Separation from family and minimum communication with colleagues were causes of depression (43). For nurses with children, they also experienced various psychosocial problems related to social isolation, such as fear and distress (51, 59).…”
Section: Meta-synthesis Of Qualitative Datamentioning
confidence: 99%